DETERMINANTS OF PROFITABILITY IN ENERGY SECTOR COMPANIES LISTED ON IDX - Yuwono, Wisnu; Marthin, Ricko; Marheni, Dewi Khornida (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This study aims to determine the effect of liquidity, firm size, working capital, efficiency, leverage and sales growth on profitability due to fluctuations in company performance on the energy index listed on the IDX. The sample used in this study was 240 financial statements of companies listed on the energy index. This study uses several indicators to measure such as the independent variables used, namely current assets, total sales, net working capital, working capital turnover, debt to equity ratio and sales growth. While the dependent variable used is return on assets. The data collection was obtained from the official IDX website and the sampling technique used was purposive sampling. In processing the sample data, this study used the eviews 12 program and the method used was the multiple linear regression method. In addition to obtaining statistical tests, this study uses the SPSS 25 program. Based on the results it can be concluded that liquidity, leverage and sales growth do not have a significant effect on profitability, while firm size and efficiency have a significant positive effect on profitability. In contrast to working capital which has a significant negative effect on profitability.